NECROTIZING FASCIITIS: DIFFICULTIES ON THE WAY TO DIAGNOSING TACTICS - Korikhonov, D.N.; Boboev, K.Kh.; Abdurakhmanov, F.M.; Okhunov, A.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. The new early diagnosis of necrotizing fasciitis, and, consequently, the key to successful treatment of these severe patients, to date, is still a timely thorough analysis of anamnestic data and clinical symptoms. At the same time, there is no reliable data on the clinical significance of various symptoms of necrotizing fasciitis, as well as on specific signs of varieties of such infections in the literature. Material. The clinical picture and features of the course of necrotizing fasciitis in 45 patients who were treated and examined in the multidisciplinary clinic of the Tashkent Medical Academy from 2020 to 2022 were analyzed. Conclusion. In the early stages of the disease, the diagnosis of necrotizing soft tissue infection can almost always be established based on an assessment of the clinical picture of the disease. Conducting an additional examination (ultrasound, computed tomography, radiography) is advisable only with a dubious clinical picture and the absence of a pronounced increasing syndrome of a systemic inflammatory reaction. Diagnostic puncture is not an informative diagnostic method for necrotizing infections. Differential diagnosis of necrotizing soft tissue infection should be carried out with several infectious and non-infectious lesions. If suspicions of necrotizing infection persist, surgical revision of all layers of soft tissues is indicated.